# Verex form of a quadratic function

## 1 Answer

We will do this by factoring the coefficient of $x^2$ first and then completing the square:

\[f(x)=-4x^2+4x+3=-4(x^2-x-\frac{3}{4})\]

\[=-4(x^2-x+\frac{1}{4}-\frac{3}{4}-\frac{1}{4})\]

\[=-4(x^2-x+\frac{1}{4}-1)\]

\[=-4((x-\frac{1}{2})^2-1)\]

\[=-4(x-\frac{1}{2})^2+4,\]

which is in the vertex form.

Poincare

133

Join Matchmaticians Affiliate Marketing
Program to earn up to a 50% commission on every question that your affiliated users ask or answer.

- 1 Answer
- 316 views
- Pro Bono

### Related Questions

- Use Rouche’s Theorem to show that all roots of $z ^6 + (1 + i)z + 1 = 0$ lines inside the annulus $ \frac{1}{2} \leq |z| \leq \frac{5}{4}$
- Linearly independent vector subsets.
- Let $z = f(x − y)$. Show that $\frac{\partial z}{\partial x}+\frac{\partial z}{\partial y}=0$
- Differentiate $f(x)=\int_{\tan x}^{0} \frac{\cos t}{1+e^t}dt$
- Module isomorphism and length of tensor product.
- Linear Algebra - Matrices (Multiple Choice Question) (1st Year College)
- How do you do absolute value equations with inequalities?
- Reverse this equation/function (2d to isometric)